2020
DOI: 10.15421/2020_171
|View full text |Cite
|
Sign up to set email alerts
|

Species composition of microbiota of cows udder and raw milk quality at mastitis

Abstract: To increase the productivity of cows and improve the nutritional and sanitary-technological qualities of milk is one of the most important tasks in the development of dairy farming in all countries of the world. The cause of degradation of these parameters is such a widespread disease of cows as mastitis. The social significance of mastitis is manifested in the fact that the causative agents of mastitis in cows can cause disease in humans. Since streptococci and staphylococci play a leading role in mastitis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It should be borne in mind that the lactation reflex may be inhibited or not manifested because of sharp noises and brutal treatment of cows. In such cases, the endocrine glands secrete the hormone adrenaline, which sharply narrows the milk ducts and delays the secretion and movement of oxytocin, as a result of which the cow 'does not entirely let down' milk (Gross & Bruckmaier, 2019;Palii et al, 2020g).…”
Section: Resultsmentioning
confidence: 99%
“…It should be borne in mind that the lactation reflex may be inhibited or not manifested because of sharp noises and brutal treatment of cows. In such cases, the endocrine glands secrete the hormone adrenaline, which sharply narrows the milk ducts and delays the secretion and movement of oxytocin, as a result of which the cow 'does not entirely let down' milk (Gross & Bruckmaier, 2019;Palii et al, 2020g).…”
Section: Resultsmentioning
confidence: 99%
“…Although Ladyka (1999) and Ovcharenko (2000) have determined that an increase in the proportion of heredity of the improving Holstein breed has a positive effect on milk's average protein content and its qualitative composition, until now, scientists have obtained the results of the influence of several factors (genetic and non-genetic) on the change in the protein content in milk of cows in previously created breeds (Palii et al, 2020f). A comparative assessment of the results of these studies indicates their diversity.…”
Section: Influence Of Cattle Breed Combinations On Milk Productionmentioning
confidence: 99%
“…Escherichia coli strains were resistant to ofloxacin in more than 95.0% of cases (Kasianchuk et al, 2018). Studies of antibiotic resistance of strains from the udder of cows with mastitis suggested that long presence of yeast cultures in the microbiocenosis together with E. coli cultures increases the antibiotic resistance of the latter (Kalashnikov, 2011), while in about 30.0% of cows with mastitis, E. coli was isolated from milk (Palii et al, 2020).…”
Section: Escherichiosis (E Coli Including Stec)mentioning
confidence: 99%